Illegal Halal Products and Legal Protection of MSME Consumers in Karanganyar - Zahriani, Lutfiana; Evi; Mekarsari, Anisa (Islam Transformatif : Journal of Islamic Studies, 2025)
The practice of including halal labels without official certification is still common, which has the potential to mislead consumers. This study aims to analyze the practice of including illegal halal labels by MSMEs and examines the form of legal protection for affected consumers. The uniqueness of this study lies in the focus of the survey of MSMEs in local public spaces and consumer responses to illegal labeling. The method was qualitative field research, with data collection techniques through observation, interviews, and documentation. Data analysis used an interactive model, which includes data reduction, data presentation, and concluding. The results of the study showed that many MSMEs include halal labels illegally, and consumer responses vary between supporting and rejecting. Legal protection for consumers is regulated in Law No. 8 of 1999, Law No. 33 of 2014, and PP No. 42 of 2024, with administrative sanctions for business actors who violate. The theoretical implication of this study lies in its contribution to the discourse on legal awareness and informal regulatory practices, while practically it provides targeted insights for local authorities to improve enforcement in MSME-dominated public areas; the primary distinction of this paper is its localized focus on consumer protection in grassroots halal governance.